Colombia: Public capital and manufacturing productivity - Sergio Jiménez R.; Jaime Sanaú V. (CEPAL Review, 2011)
The work described in this article takes an approach based on duality theory to examine the impact of public infrastructures on manufacturing productivity in Colombia between 1990 and 2005. The effect on the manufacturing cost structure of public capital investment is analysed by means of the substitution or complementarity among the various factors of private production and public capital.